2007
DOI: 10.1096/fasebj.21.5.a241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preparations from the skin of the Arabian Gulf catfish (Arius bilineatus Val.) on back pain and other related pain

Abstract: Preparations from the skin of the Arabian Gulf catfish involving biologically active proteins and lipids exhibit profound effects on healing of back pain and other related types of pain, when applied topically once every 24 hrs for 3‐7 days. The preparations seem to act on inflammation, and demyelination in the nervous tissues as well as repair damage to soft tissues. Treated cases included cervical, thoracic, lumber, sacral, knee and foot joint pain. Carpal tunnel syndrome and pain in the lower limbs related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…Sheep red blood cells also showed variability similar to that noted for human type O cells. Several studies have convincingly established that the repeated application of preparations involving catfish epidermal secretions to wounds and persistent diabetic foot ulcers in human subjects had a positive effect on wound healing (Al‐Hassan, 1990; Al‐Hassan et al., 1991). The complex mixture of components contained in the epidermal secretion obviously induces a balanced stimulation of the early stages of wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep red blood cells also showed variability similar to that noted for human type O cells. Several studies have convincingly established that the repeated application of preparations involving catfish epidermal secretions to wounds and persistent diabetic foot ulcers in human subjects had a positive effect on wound healing (Al‐Hassan, 1990; Al‐Hassan et al., 1991). The complex mixture of components contained in the epidermal secretion obviously induces a balanced stimulation of the early stages of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Their functions are not well defined, but some protective roles have been suggested (Cameron and Endean, 1973; Al‐Hassan et al., 1985). Several studies also provided evidence that preparations from the skin secretions of A. bilineatus can stimulate the rate of wound healing in animals and healing of diabetic foot ulcers in humans (Al‐Hassan et al.,1983,1985,1987a,b, 1991; Al‐Hassan, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Application of fish mucus on mammalian wounds may activate healing (Al‐Hassan et al . 1983; Al‐Hassan 1990; Al‐Hassan et al . 1991; Akunne et al .…”
Section: The Anatomy and Functions Of Fish Skinmentioning
confidence: 99%
“…These fish that are often wounded by marine predators, developed the unique mechanism by which they are able to effectively heal their wounds (Al-Hassan et al, 1985). This curious observation initiated a series of studies directed by one of us [JA-H] (Al-Hassan et al, 1983;Al-Hassan et al, 1991) that established PCEGS preparations could accelerate wound healing (Al-Hassan et al, 1983;Al-Hassan et al, 1991), and were found effective in treating human chronic diabetic foot ulcers that were unresponsive to conventional therapy (Al-Hassan, 1990). Biochemical analysis has shown that the PCEGS preparations, used in the initial studies, contained several biologically active proteins, including growth factors (Al-Hassan et al, 1986;Al-Lahham et al, 1987;Thomson et al, 1989) and lipids (Al-Hassan et al, 1986;Plattner et al, 1988;Summers et al, 1991;Al-Hassan et al, 1998;Khan et al, 2018;Al-Hassan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%